2016
DOI: 10.4038/ss.v43i1-2.4690
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Transmission Mechanism in Sri Lanka: A Comprehensive Assessment with New Evidence

Abstract: This study provides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 111 publications
(179 reference statements)
2
4
0
Order By: Relevance
“…Tang (2006) also found that the interest rate is important in influencing both output and inflation. This was consistent with Srithilat and Sun (2017) and Perera (2016). However, Ufoeze (2018) found that the monetary policy rate and the interest rate have an insignificant positive relationship on economic growth.…”
Section: Literature Reviewsupporting
confidence: 92%
“…Tang (2006) also found that the interest rate is important in influencing both output and inflation. This was consistent with Srithilat and Sun (2017) and Perera (2016). However, Ufoeze (2018) found that the monetary policy rate and the interest rate have an insignificant positive relationship on economic growth.…”
Section: Literature Reviewsupporting
confidence: 92%
“…This may be due to uncompetitive market forces and higher switching costs in the deposit market than in the lending market (Horváth et al 2004). These pass-through magnitudes for LR and DR are quite similar to those obtained by Perera (2016), who calculated pass-through rates of approximately 98 percent and 63 ppercentrespectively for the 2001-2012 subsample period in the Sri Lankan context.…”
Section: Econometric Approachsupporting
confidence: 86%
“…As a developing economy, Sri Lanka experiences higher volatility in the interbank market, mainly due to commercial banks' involvement in foreign exchange operations and fiscal financing through state commercial banks. Hence, the interbank money market rate may not be the best proxy for the policy rate in this case (Perera 2016). Furthermore, Fuertes & Heffernan (2009) argue that the money market rate is not a good proxy for the policy rate because it is driven largely by the demand and supply of the interbank fund.…”
Section: Datamentioning
confidence: 99%
“…This price puzzle refers to a positive interest rate shock leading to an initial increase in the price level, rather than a reduction (Sims, 1992;Christiano, Eichenbaum & Evans, 1994;Balke & Emery, 1994). Furthermore, the research studies by Arin and Jolly (2005) covering Australia and New Zealand and Perera (2016) for Sri Lanka also showed a positive relationship between the interest rate and inflation. Several studies have included other variables, such as commodity prices (Hanson, 2004) or the output gap (Bonga-Bonga & Kabundi, 2011) in order to overcome the problem of the price puzzle.…”
Section: Empirical Evidence On the Relationship Between The Monetary Policy Fiscal Policy And Inflationmentioning
confidence: 87%